Factors influencing the purchase of regional wines by the Millennial generation from the Lubusz Voivodeship - Michałowska, Mariola; Kułyk, Piotr (Zielona Góra: Faculty of Economics and Management Press)
The main aim of the study is to identify the most important conditions favoring the development of the Lubusz wine market, with particular emphasis on examining the involvement of young buyers (Millennium generation) in the purchase of Lubusz wines and the impact of factors determining their behavior, including situational ones related to the purchase and consumption of wine, as a generation in an increasingly more responsible for expanding the market.
Keywords: Millennial generation; determinants; regional wine; consumption of wine; Lubusz Voivodeship